Dust Entrainment in Photoevaporative Winds: Densities and Imaging - Perez-Marquez, S (EDP Sciences, 2022)
Context. X-ray- and extreme-ultraviolet- (together: XEUV-) driven photoevaporative winds acting on protoplanetary disks around young T-Tauri stars may crucially impact disk evolution, affecting both gas and dust distributions. Aims. We constrain the dust densities in a typical XEUV-driven outflow, and determine whether these winds can be observed at μm-wavelengths. Methods. We used dust trajectories modelled atop a 2D hydrodynamical gas model of a protoplanetary disk irradiated by a central T-Tauri star. With these and two different prescriptions for the dust distribution in the underlying disk, we constructed wind density maps for individual grain sizes. We used the dust density distributions obtained to synthesise observations in scattered and polarised light. Results. For an XEUV-driven outflow around a M∗ = 0.7 M⊙ T-Tauri star with LX = 2 × 1030 erg s-1, we find a dust mass-loss rate Ṁ dust ≲ 4.1 × 10-11 M⊙ yr-1 for an optimistic estimate of dust densities in the wind (compared to Ṁ gas ≈ 3.7 × 10-8 M⊙ yr-1). The synthesised scattered-light images suggest a distinct chimney structure emerging at intensities I∕ Imax < 10-4.5 (10-3.5) at λobs = 1.6 (0.4) μm, while the features in the polarised-light images are even fainter. Observations synthesised from our model do not exhibit clear features for SPHERE IRDIS, but show a faint wind signature for JWST NIRCam under optimal conditions. Conclusions. Unambiguous detections of photoevaporative XEUV winds launched from primordial disks are at least challenging with current instrumentation; this provides a possible explanation as to why disk winds are not routinely detected in scattered or polarised light. Our calculations show that disk scale heights retrieved from scattered-light observations should be only marginally affected by the presence of an XEUV wind. © ESO 2022.